2019
DOI: 10.21203/rs.2.17508/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Albumin to alkaline phosphatase ratio: does it predict survival in grade 1 and grade 2 neuroendocrine tumors?

Abstract: BACKGROUND: Neuroendocrine tumors (NETs) are very heterogeneous tumors. Although it is classified according to Ki-67 proliferation index and mitotic count, their behavior may greatly vary even in the same group. Therefore, more accurate prognostic markers are required to predict prognosis in patients with well differentiated NETs. This study is aimed to evaluate prognostic value of albumin to alkaline phosphatase ratio (AAPR) in patients with well differentiated neuroendocrine tumors. PATIENTS AND METHODS: A t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Since Chan et al (16) first introduced this simply synthetic biomarker based on sALB and serum ALP for estimating the outcome of the procedure in hepatocellular carcinoma, AAPR has been widely demonstrated to be promisingly indicative of post-treatment prognosis in a series of malignant tumors, including nasopharyngeal carcinoma (17), urothelial carcinoma (18), cholangiocarcinoma (19), lung cancer (12,20), bladder cancer (21), and pancreatic cancer (22,23). Several recent evidence-based literature reviews have also provided comprehensive results suggesting a potent prognostic impact of AAPR in human solid tumors, regardless of their histological origins (15,24).…”
Section: Key Results and Interpretationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Chan et al (16) first introduced this simply synthetic biomarker based on sALB and serum ALP for estimating the outcome of the procedure in hepatocellular carcinoma, AAPR has been widely demonstrated to be promisingly indicative of post-treatment prognosis in a series of malignant tumors, including nasopharyngeal carcinoma (17), urothelial carcinoma (18), cholangiocarcinoma (19), lung cancer (12,20), bladder cancer (21), and pancreatic cancer (22,23). Several recent evidence-based literature reviews have also provided comprehensive results suggesting a potent prognostic impact of AAPR in human solid tumors, regardless of their histological origins (15,24).…”
Section: Key Results and Interpretationsmentioning
confidence: 99%
“…Alkaline phosphatase (ALP), another hydrolase widely accepted as a disease marker of the hepatobiliary system, bone, and kidney, has also been correlated with postoperative survival of cancer patients (15). In summary, a novel and simple scoring system by integrating sALB with serum ALP, named albumin-toalkaline phosphatase ratio (AAPR), has been constantly validated as a reliable prognostic indicator across a wide range of malignant tumors, regardless of their treatment options (12,(16)(17)(18)(19)(20)(21)(22)(23)(24). However, to our knowledge, the potential prognostic value of AAPR has not yet been explored in patients undergoing esophagectomy for EC.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…AAPR was applied in patients undergoing surgery for hepatocellular carcinoma for the first time by Chan et al; this conclusion has been confirmed in the following studies [ 35 , 36 ]. Furthermore, previous research has shown that low levels of this indicator are associated with poor outcomes [ 37 , 38 ]. Despite varying cutoff values, these studies confirm that patients with high AAPR have a better prognosis than those with low AAPR.…”
Section: Discussionmentioning
confidence: 99%
“…AAPR is the ratio of ALB to ALP. Several studies have demonstrated that low AAPR is strongly associated with poor prognosis in malignancies [6,[30][31][32][33].…”
Section: Figurementioning
confidence: 99%